Open Source Plagiarism Checking Software: An Assessment of Awareness and Utility Among Social Science Research Scholars of Lalit Narayan Mithila University, Darbhanga, Bihar: A Study (LIS TODAY, 2024)
This study investigates the awareness and usage of open-source plagiarism  checking software among research scholars in the Social Sciences discipline  at Lalit Narayan Mithila University (LNMU), Darbhanga, Bihar. Given the  increasing importance of academic integrity, this study aims to identify the  level of knowledge, usage patterns, and perceived benefits of these tools among  researchers. A structured questionnaire was administered to 60 participants,  revealing a moderate level of awareness but limited usage. The findings  suggest the need for enhanced training and institutional support to promote  the effective use of open source plagiarism detection software. Although there  is a notable intention to use plagiarism detection resources, various barriers  remain that must be addressed to optimize their utilization and reinforce  academic integrity in research practices.
Keywords: Open Source Software; Plagiarism; Plagiarism Checking Software; Social Science Researchers; Lalit Narayan Mithila University; LNMU